CREATIVE ACCOUNTING AND ITS IMPACT ON THE FINANCIAL INFORMATION - Cruz Ramírez, Dorie (2012)
The accounting manipulation or creative accounting is a current topic, it is widely practiced but little combated: altering benefits. Activity has been done for years by various countries, as if it were a game, the truth is that its nature and consequences is a topic of great interest, since an opportunistic accounting choice taken by the management of a company can lead to certain individuals are privileged at the expense of others. How to hide debt off balance, how to alter items of income and expenses. According to an investigation by the Securities and Exchange Commission in the U.S., more than half of the financial abuse of the 90’s were due to incorrect policies for revenue recognition. The influence of accounting manipulation on financial and equity structure has an impact on the truth of financial reporting and thus accounting for the valuation of the economic unit. The subjectivity of different accounting treatments for determining the financial information is crucial to be open to abuse and how different consolidation policies have been used and abused until to generate significant accounting scandals.